The Influence of Individual Auditor Factors on the Auditor's Ability to Detect Fraud with Whistleblowing as a Moderating Variable - Lidya Sampepolan, Febriyanti; Herawaty, Vinola; Caeshara, Monica (Journal of World Science, 2023)
The role of the auditor is crucial in analyzing the occurrence of fraud. This study investigates the effect of professional scepticism, independence, and competence on the auditor's ability to detect fraud, with whistleblowing as a moderating variable. The study population was composed of junior and senior auditors at BPK RI. The data in this study were collected through questionnaires. This type of study is hypothesis testing research. The number of samples collected was 157. The pieces were determined by the convenience sampling method. The results of the survey show that professional scepticism has no positive effect on the auditor's ability to detect fraud, independence has a positive impact on the auditor's ability to detect fraud, the auditor's competence has no positive effect on the auditor's ability to detect fraud, whistleblowing does not moderate the impact of professional scepticism on the auditor's ability to detect fraud, whistleblowing does not moderate the impact of independence on the auditor's ability to detect fraud, and whistleblowing does not moderate the effect of the auditor's competence in detecting fraud.